1985
DOI: 10.1515/cclm.1985.23.11.725
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Theophylline in Saliva, Using Fluorescence Polarization Immunoassay (FPIA)

Abstract: Theophylline concentrations were determined by fluorescence polarization immunoassay (FPIA) in saliva, serum and serum water of healthy volunteers and outpatients after administration of single , theophylline doses, and after the administration of several doses in order to establish a steady state. The ! FPIA allowed rapid and reliable theophylline determinations in saliva and serum water (between-days j coefficients of Variation: < 3%; recovery: 95 -103%). Salivary theophylline concentrations measured by l, '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…However theophylline also stimulates the central nervous system (Kumer, 2004). Several studies have shown improvement of performance in racehorses 644 F. Beaudry et al ORIGINAL RESEARCH and fluorescence polarization immunoassay (Niemann, et al, 1985). All these methods lack precision and accuracy and are mainly used for screening purposes.…”
Section: Introductionmentioning
confidence: 99%
“…However theophylline also stimulates the central nervous system (Kumer, 2004). Several studies have shown improvement of performance in racehorses 644 F. Beaudry et al ORIGINAL RESEARCH and fluorescence polarization immunoassay (Niemann, et al, 1985). All these methods lack precision and accuracy and are mainly used for screening purposes.…”
Section: Introductionmentioning
confidence: 99%
“…The lower limit of the measured range was 0.5 mg/1. With this immunoassay the relative standard deviation between days was 3.6% over the mid-part of the measuring range (13,14). The performance of the FPIA was constantly checked by internal and external quality control.…”
Section: Determination Of Serum Theophylline Concentrationsmentioning
confidence: 92%
“…So far, the existence of this phenomenon has been shown for 2 examples: ethanol (56) and caffeine (57). However, they have interpreted their results by back diffusion from the oral mucosa (60,61). Theophylline is another candidate (40).…”
Section: Phenomenon Of Varying Arteriovenous Differencesmentioning
confidence: 99%